Letter to Jane Tolmach; from Louis R. Nash - Louis R. Nash:::::: (1963)
Letter to Jane Tolmach from Louis R. Nash (Superintendent and Medical Director) sent on April 15, 1963. Louis R. Nash sent Jane Tolmach a two page letter showing in detail the efforts, developments, and history about Dr. Garrett and the impact he's had in State Hospitals. It seems to be a guidance letter for Jane to create a resolution honoring Dr. Garrett's service that the Board is asking all trustees to prepare.